1985
DOI: 10.1113/expphysiol.1985.sp002888
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Variation in Phosphorus Intake on Net Intestinal Phosphorus Absorption, Salivary Phosphorus Secretion and Pathway of Excretion in Sheep Fed Roughage Diets

Abstract: Quarterly Journal of Experimental Physiology 69–3 (1984) On page 448 the sentence 3 lines from the bottom should read The sheep were fitted with a re‐entrant cannula in the duodenum close to the pylorus and digesta was collected through this cannula for 30 h after dosing, unlabelled donor material being used to replace that removed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 0 publications
4
17
0
2
Order By: Relevance
“…Furthermore, P concentration in plasma was related to endogenous P excreted in feces (F"2e. "a; r = 0.71, P < 0.01), indicating greater P in plasma might have induced a greater secretion of endogenous P (Mañas-Almendros et al, 1982;Scott et al, 1984) and, consequently, a greater excretion in feces. In agreement with Preston and Pfander (1964) and Vitti et al (2005), endogenous (also called metabolic) fecal P increased with increasing dietary P. Endogenous fecal P can be derived either from inevitable fecal losses or from fecal excretion of surphis P (Pfeffer et al, 2005).…”
Section: P Intake Excretion and Secretionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, P concentration in plasma was related to endogenous P excreted in feces (F"2e. "a; r = 0.71, P < 0.01), indicating greater P in plasma might have induced a greater secretion of endogenous P (Mañas-Almendros et al, 1982;Scott et al, 1984) and, consequently, a greater excretion in feces. In agreement with Preston and Pfander (1964) and Vitti et al (2005), endogenous (also called metabolic) fecal P increased with increasing dietary P. Endogenous fecal P can be derived either from inevitable fecal losses or from fecal excretion of surphis P (Pfeffer et al, 2005).…”
Section: P Intake Excretion and Secretionmentioning
confidence: 90%
“…Although it is considered negligible, P excretion in urine of ruminants contributes to P homeostasis. According to various studies (Field et al, 1983;Scott et al, 1984;Scott and Buchan, 1985), when plasma P increases above a concentration threshold (about 2 mmol/L), the reabsorptive capacity of kidney tubules is exceeded and extra P is excreted in urine. In this sttidy, plasma P concentrations were above this concentration (2.15, 2.55, 2.83, and 2.81 mmol/L for LP, MP, HP, and SP, respectively).…”
Section: P Intake Excretion and Secretionmentioning
confidence: 97%
“…In sheep, the upper small intestine is the major absorptive site with both active transport and passive diffusion mechanisms (Care, 1994). With perfusion of the temporarily isolated upper small intestine with NaH 2 PO 4 (5 to 50 mmol/L), Scott et al (1984) reported a curvilinear relationship between P absorption and P concentration; absorption efficiency fell from 0.74 at 5 mmol/L to 0.35 at 50 mmol/L. It was also reported that in sheep, as dietary P increased from 2.5 to 5.0 g/kg of DM, total P absorbed increased but efficiency of absorption was constant (Bravo et al, 2003a,b).…”
Section: Digestion and Absorption Of P In The Digestive Tractmentioning
confidence: 99%
“…Salivary P was estimated as the difference between duodenal P flow and P intake (Scott et al, 1984(Scott et al, , 1985Scott and Buchan, 1987). In monogastrics, the kidneys are most important in removing excess P from the blood, whereas, in ruminants, the salivary glands play this role (Care, 1994).…”
Section: Salivary P Secretionmentioning
confidence: 99%
See 1 more Smart Citation